2014
DOI: 10.1007/s40653-014-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Problem Solving Skills in the Relationship between Traumatic Stress and Moral Disengagement among Inner-City African American High School Students

Abstract: This study examined the relationship between traumatic stress, social problem solving, and moral disengagement among African American inner-city high school students. Participants consisted of 45 (25 males and 20 females) African American students enrolled in grades 10 through 12. Mediation was assessed by testing for the indirect effect using the confidence interval derived from 10,000 bootstrapped resamples. The results revealed that social problem-solving skills have an indirect effect on the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
3
0
6
Order By: Relevance
“…Moreover, social problem solving skills have produced positive behaviour and social competence and reduce negative behaviour such as conduct problems, Social Problem-Solving Skills in Children: An Exploratory Study aggressive behaviour, stress etc. (Dubow, Tisak, Hrvshko & Reid, 1991;Biggam & Power, 1999;Pakaslahti, Karjalainen, & Keltikangas-Jarvinen, 2002;Eskin, Savk, Uslu & Kucukaydogan, 2014;Coker et al 2014;Huang et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, social problem solving skills have produced positive behaviour and social competence and reduce negative behaviour such as conduct problems, Social Problem-Solving Skills in Children: An Exploratory Study aggressive behaviour, stress etc. (Dubow, Tisak, Hrvshko & Reid, 1991;Biggam & Power, 1999;Pakaslahti, Karjalainen, & Keltikangas-Jarvinen, 2002;Eskin, Savk, Uslu & Kucukaydogan, 2014;Coker et al 2014;Huang et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Hyde et al have proposed that "repeated exposure to [morally disengaging] behavior and attitudes should eventually lead children to become morally disengaged from mainstream values and more likely to engage in antisocial activities." Furthermore, this argument is bolstered by recent work that has shown that exposure to traumatic events is related to higher levels of MD in a sample of inner city African American adolescents (Coker, Ikpe, Brooks, Page, & Sobell, 2014). These findings suggest that although MD is a psychological process, people may learn to morally disengage through interactions within their neighborhoods.…”
Section: Past Empirical Researchmentioning
confidence: 95%
“…Trauma, as defined by a person's subjective assignment of meaning, can result from a variety of experiences, and the impact of these experiences can be conceptualized as stemming from a single event (i.e., simple trauma) or multiple events (i.e., complex trauma) up to clusters of repeated traumas termed adverse childhood experiences. Simple trauma, meaning exposure to individual traumatic experiences, has been examined in terms of economic stress (Blitz, Anderson, & Saastamoinen, 2016), racial stress (Jernigan & Daniel, 2010), violence (Luthra et al, 2009), bullying (Carney, 2008), hurricanes (Hebert & Ballard, 2007), war (Burnham & Hooper, 2008), and sexual abuse (Brown, Brack & Mullis, 2008), and strategies for addressing these isolated stress sources have been discussed (e.g., Blitz et al, 2016;Cohen & Mannarino, 2008;Coker, Ikpe, Brooks, Page, & Sobell, 2014;Gudiño, Leonard, & Cloitre, 2016;Openshaw, 2011). Additional insights have been developed relative to complex trauma, which results from severe, co-occurring, or recurring trauma events that occur within the caregiver system or with another trusted adult beginning in childhood or adolescence (Lawson & Quinn, 2013).…”
mentioning
confidence: 99%